PENINGKATAN MOTORIK HALUS ANAK USIA 4-5 TAHUN MELALUI IMPLEMENTASI MEDIA PELEPAH PISANG DI TK MAMBAUL ULUM - Hasanah, Ivadatul; Pipit Rika Wijaya; Rizki Sevi Triana; Mochammad Maulana Trianggono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem that occurred in the Mambaul Ulum Kindergarten institution was that there were still some children when coloring still outside the lines and were still not neat in coloring. Of the 13 students there were 7 children who still needed stimulation in improving fine motor skills, especially in eye and hand coordination. This happened because of the lack of variation in the media used, children's interest decreased because the learning media used was monotonous, the lack of independence in children also caused children to have dependence on others. Through specific acts, such as using banana stem media to help youngsters develop their fine motor abilities, the study aimed to improve and enrich the learning process in the classroom. This study used Classroom Action Research (CAR) according to the Kemmis and McTaggart CAR paradigm, which has two cycles with two meetings each. Group A of 13 pupils from Mambaul Ulum Kindergarten served as the study's subject. Based on the results of initial observations, there were 7 children or 54% of the 13 children in group A who were not yet able to coordinate their eyes and hands in the category (Not Developing), after the implementation of banana stem media, After two sessions, there was an increase in cycle I, with 4 children, or 31% of the total, falling into the category of "Developing According to Expectations." Cycle II of the research was conducted since cycle I required more action. There was an increase in the motor skills of the children in cycle II; 10 children, or 80% of the total, fell into the category of "Developing According to Expectations." Because 80% of the children's success criteria had to be reached for the research to be considered successful, cycle II was terminated.